A molecular phylogenetic study of Cucujidae s.l. (Coleoptera: Cucujoidea). (10th June 2015) - MCELRATH, THOMAS C.; ROBERTSON, JAMES A.; THOMAS, MICHAEL C.; OSBORNE, JONATHAN; MILLER, KELLY B.; MCHUGH, JOSEPH V.; WHITING, MICHAEL F.
Abstract Of all the superfamilies within the megadiverse order Coleoptera (Insecta), Cucujoidea (Cucujiformia) is arguably the most problematic taxonomically. The families comprising Cucujidae s.l. (Silvanidae, Laemophloeidae, Passandridae and Cucujidae s.s. represent a large portion of cucujoid diversity. Herein we present the results of a rigorous molecular phylogenetic analysis of Cucujidae s.l. using maximum‐likelihood and Bayesian analyses of seven genes. Representatives of over half of the families of Cucujoidea (excluding the cerylonid series), as well as a broad sampling of Silvanidae and Laemophloeidae, were analysed. The monophyly of Cucujidae s.l. is rejected but a subgrouping of taxa that may form the core of a natural cucujoid lineage is recovered. This clade consists of two large monophyletic groups including several families each. Relationships among these smaller cucujoid groups are discussed, including several novel phylogenetic hypotheses, whereas morphological characters considered significant for classification in Cucujidae s.l. are evaluated in light of these phylogenetic hypotheses. Silvaninae, Telephanini, Brontini and Brontinae are recovered as monophyletic in the Bayesian analysis, but the former two are recovered as paraphyletic in the maximum‐likelihood analysis. Our results support the placement of Psammoecus Latreille within Telephanini and also recover a paraphyletic Telephanus Erichson. Silvaninae is divided into three lineages, each representing a potential tribal lineage. Laemophloeidae is rendered paraphyletic in all analyses by Propalticidae and the latter is herein formally transferred to Laemophloeidae stat.n. Several suprageneric laemophloeid clades are recovered and discussed as potential higher‐level groups. Laemophloeus Dejean is not recovered as monophyletic.